Factors Influencing the Income of Micro, Small, and Medium Enterprises (MSMEs) in Denpasar City - I Made Bagus Ananta Wiguna; Ni Putu Martini Dewi (International Journal of Economics, Management and Accounting, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the economy, particularly in areas like Denpasar City, which serves as a central hub of economic activity in Bali. However, the COVID-19 pandemic posed significant challenges, severely impacting MSMEs’ net income. Declining purchasing power, mobility restrictions, and economic uncertainty forced business owners to struggle for survival. This highlights the need to understand the factors affecting MSMEs’ income in order to formulate strategic solutions. This study employs a quantitative associative approach to examine the influence between two or more variables. A sample of 100 MSMEs was selected using a proportional stratified random sampling technique based on the distribution of MSMEs across districts and business types. The results show that own capital, pricing, working hours, and access to the People's Business Credit (KUR) significantly affect MSME income in Denpasar City. Own capital is found to be the most dominant factor, followed by pricing and working hours. Access to KUR also plays an important role by providing easier access to additional capital, enabling business expansion and productivity improvement. Furthermore, the study confirms that competitive pricing and effective pricing strategies can enhance competitiveness and increase income. Longer working hours positively influence income by providing more opportunities to serve customers. Overall, access to KUR facilitates capital availability, ultimately supporting MSME growth and income in Denpasar City. Keywords: MSME Income, Denpasar City